PENGEMBANGAN MODEL PEMBELAJARAN BAHASA INDONESIA BERBASIS PROYEK DI ERA REVOLUSI INDUSTRI 4.0 - Fitria, Yenni; Rachayu, Imma (Jurnal Pendidikan Bahasa dan Sastra, 2019)
The Industrial Revolution Era 4.0 requires students to think creatively and critically in order to practice independent thinking. These requirements are contrary to Indonesian language learning for students of Informatics and Computer Engineering FKIP Dehasen University Bengkulu. This development research aims to develop an effective project-based Indonesian learning model so that learning is more meaningful. Development with three steps of work and data collection by observation, interview and questionnaire. Data analysis techniques are qualitative and quantitative. The results showed that 1) the implementation of the learning model "in accordance" aspects of learning with the category of "good", the average result of the 96% observation count. 2) Student activities in "active" learning with observational results of 90%. 3) Student responses are positive or "agree" about the practicality of the project learning model with the results of the questionnaire count 83%. The project-based Indonesian learning model is effectively used for Indonesian language courses at FKIP Dehasen University Bengkulu through limited trials with an effectiveness calculation result of 93%.